Roles And Responsibilities Of Land Agreement Official Tax Administration BPHTB in The Sale And Purchase Transactions Over Land And Building In Semarang - Armina Dilla Zahirani; Aryani Witasari (Program Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam Sultan Agung, 2018)
On Article 91 paragraph 1 of Act No. 28 of 2009 on Local Taxes and Levies otherwise PPAT can only sign the agreement of transfer of rights to land and or building after the taxpayer to submit proof of payment of taxes, in the form of Tax Payment (SSP) of the Sellers and Slip Tax on Acquisition of Land and Building (SSB) of the Purchaser, The question that arises from this problem is: What is the Role and Responsibility of the Agreement Official Land in Tax Administration BPHTB Transaction Purchase land or buildings in the city, How Procedure of Tax Administration BPHTB of the transaction Purchase land or buildings in the city, Constraints and Fighting in BPHTB Tax Administration on Sale and Purchase Transactions land and or building in the city of Semarang. Juridical approach method using empiris.Data used are primary and secondary data. Methods of data collection using interviews and literature. Methods of data analysis using qualitative analysis.The location was selected the city, for the samples taken 2 PPAT, Regional Revenue Agency Semarang and 2 taxpayers. The sampling technique was conducted by purposive sampling. Tools data collection conducted by interviews and document study.Keywords: PPAT; Acquisition of Land and Building (BPHTB); Purchase.